E-013 Endovascular Management of Pseudoaneurysms Secondary to External Ventricular Drain Placement: Single Center Experience. (26th July 2014) - Choudhri, O; Gupta, M; Heit, J; Feroze, A; Do, H
Abstract : Introduction: Placement of external ventricular drains is a common, life-saving neurosurgical procedure indicated across a variety of settings. While advances have made the procedure quite safe, the potential for iatrogenic morbidity and mortality continues. Herein, we document our experience with the endovascular management of three pseudoaneurysms associated with EVD placement. Patients and methods: We performed a retrospective analysis to identify all EVDs placed from 2008 through 2013 at our institution, . In instances of EVD-associated cerebrovascular injury, all admission and subsequent radiographic studies were reviewed, including cerebral angiograms and computed tomography (CT) scans. Angiograms were reviewed to record the extent of vascular injury and angiographic outcomes after treatment. Results: One female and two male patients (40–75 years) were found to have developed vascular injuries associated with EVD placement. Three pseudoaneurysms, namely of the posterior communicating artery (PCOM), pericallosal artery branch and the middle meningeal artery, were treated by coil and/or glue embolization. Conclusions: Although EVD-associated cerebrovascular injury remains a rare phenomenon, such procedures are not entirely benign. Endovascular repair for such lesions proves a viable, effective option. Abbreviations: arteriovenous fistula (AVF), computed tomography (CT), external ventricular drain (EVD), posterior communicating artery (PCOM), posterior cerebral artery (PCA) Disclosures: O. Choudhri: None. M. Gupta: None. J. Heit: None. A. Feroze: None. H. Do: None.